2006
DOI: 10.4049/jimmunol.177.1.192
|View full text |Cite
|
Sign up to set email alerts
|

Indexation as a Novel Mechanism of Lymphocyte Homeostasis: The Number of CD4+CD25+ Regulatory T Cells Is Indexed to the Number of IL-2-Producing Cells

Abstract: To fulfill its mission, the immune system must maintain a complete set of different cellular subpopulations that play specific roles in immune responses. We have investigated the mechanisms regulating CD4+CD25+ regulatory T (Treg) cell homeostasis. We show that the expression of the high-affinity IL-2Rα endows these cells with the capacity to explore the IL-2 resource, ensuring their presence while keeping their number tied to the number of CD4+ T cells that produce IL-2. We show that such a homeostatic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
148
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 37 publications
(27 reference statements)
5
148
0
Order By: Relevance
“…Five weeks after adoptive T cell transfer, we found that upon in vivo Ag stimulation Ag-specific STAT6 Ϫ/Ϫ out-competed STAT4 Ϫ/Ϫ CD4 ϩ T cells (data not shown) as it was the case during LDP of polyclonal T cells (9). More importantly, we found that the fraction of Treg cells recovered after adoptive transfer of WT, STAT4 Ϫ/Ϫ , or STAT6 Ϫ/Ϫ TCR-HA CD4 ϩ T cells was Ͻ2% and identical in both Ag-free and HA ϩ hosts (data not shown) and indistinguishable from that of the original injected CD4 ϩ T cell population (13). This indicates that the exposure of mature peripheral HA-specific T cells to HA did not result in "de novo" generation of Foxp3 ϩ Treg cells, in contrast to what was observed when these cells developed throughout the thymus of the HA BM chimeras (see Fig.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Five weeks after adoptive T cell transfer, we found that upon in vivo Ag stimulation Ag-specific STAT6 Ϫ/Ϫ out-competed STAT4 Ϫ/Ϫ CD4 ϩ T cells (data not shown) as it was the case during LDP of polyclonal T cells (9). More importantly, we found that the fraction of Treg cells recovered after adoptive transfer of WT, STAT4 Ϫ/Ϫ , or STAT6 Ϫ/Ϫ TCR-HA CD4 ϩ T cells was Ͻ2% and identical in both Ag-free and HA ϩ hosts (data not shown) and indistinguishable from that of the original injected CD4 ϩ T cell population (13). This indicates that the exposure of mature peripheral HA-specific T cells to HA did not result in "de novo" generation of Foxp3 ϩ Treg cells, in contrast to what was observed when these cells developed throughout the thymus of the HA BM chimeras (see Fig.…”
Section: Resultsmentioning
confidence: 57%
“…In the peripheral compartments of the HA-free BM chimeras, the number of Ag-specific CD4 ϩ 6.5 ϩ T cells was similar (range from 2.9 to 3.6 ϫ 10 6 ) whether the mice were reconstituted with WT, STAT4-, or STAT6-deficient TCR-HA BM (Fig. 1b), indicating that peripheral homeostatic mechanisms operate to compensate the lower SP compartment of the STAT-deficient HA-specific T cells (13). In the BM chimeras expressing HA, the number of peripheral CD4 ϩ 6.5 ϩ T cells was reduced as compared with HA-free chimeras (12).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Our recent data do not suggest the presence of higher frequencies of regulatory T cells (CD25 high /FOXP3 ϩ ) in mangabeys (52). Low, but consistent IL-2 levels detected in SM may, however, potentiate their function (17,50,51) and limit the activation of effector T cells, therefore limiting immunopathology associated with chronic high viremia infection such as HIV or SIV. This mechanism is being addressed in ongoing studies.…”
Section: Discussionmentioning
confidence: 59%